THE MEANING OF PUJA DANCE AS A SOURCE OF LEARNING BUDDHIST EDUCATION - Santy, Dwi Tirana; Dewi, Sukhitta; Kiryono, Kiryono; Wijayanto, Gustriya (Jurnal Pencerahan, 2023)
This research aims to describe the meaning of the Puja Dance for SMB Dhamma Phala and STAB dancer Syailendra. This type of research uses descriptive qualitative methods. The data collection techniques used were interviews, observation and documentation. The validity of the data obtained was tested by data analysis using the Miles and Huberman model which consists of data collection, data reduction, data presentation, drawing conclusions and verification. The results of this research obtained significant changes in the implementation of training. The changes that occurred were like previously not knowing the Puja Dance and understanding the meaning of the Puja Dance. The meaning contained in this Puja Dance depicts seven angels who are paying respect to the Buddha, Dhamma and Sangha, respecting symbols in Buddhism, and increasing belief in Tiratana.